PENGARUH SENAM OTAK TERHADAP PENINGKATAN MOTORIK KASAR PADA ANAK USIA 4-6 TAHUN - Lina Madyastuti R; Retno Twistiandayani; Arifatul Widya Rahayu (Fakultas Ilmu Kesehatan, 2018)
Children aged 4-6 years the most prominent development is motor, motor is closely related to physical activity. Gross motor is the development of motion control through the coordinated between the nerves, brain and spinal cord. One way to optimize the use of all the dimensions of the brain is brain gymnastics. Doing brain gym is one type of nonfarmacologis therapy that serves to improve the gross motor. The purpose of this study was to the effect of brain gym on gross motor improvement in children aged 4-6 years. This research method used Quasy experimentalwith two control groups and treatment groups. Sample was selected using the Purposive Sampling method. Samples obtained as many 30 children. Independent variable in this study ware brain gym, while the dependent variable in this study was the change rough motor of children aged 4-6 years. Data collected before and after the intervention. Analysis used of the data used stastical test of Wilcoxon Signed Ranks Test with the value <0.05. The results of research showed value significant (2-tailed) = 0.001 meaning there was influence of brain gym to the increase of gross motor in children aged 4-6 years. By giving the brain gym will provide stimulation of the brain so as to improve the coordination of the eyes and hands that can improve the development of gross motor in children.